2021
DOI: 10.32523/ejpfm.2021050103
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms formation of electron-hole trap centers in LiKSO4 crystall

Abstract: The mechanisms of creation of electron-hole trapping centers in LiKSO4 have been investigated by the methods of vacuum and thermal activation spectroscopy. It is shown that electron-hole trapping centers are formed during the trapping of electrons by anionic complexes and localization of a hole in the lattice in the form of the radical SO4−. The appearance of phosphorescence at 3.0-3.1 eV, 2.6-2.7 eV and 2.3-2.4 eV confirms the creation of electron-hole trap centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Such high efficiency indicators, which are 1.3-2 times higher than the same for the composition 0.5TeO 2 -0.4Bi 2 O 3 -0.1WO 3 are due not only to the change in glass density, but also to the electronic configuration and vacancy density, and therefore to the value of Z e f f , which directly depends on the glass composition. The data obtained are also in good agreement with the literature data [18][19][20] devoted to the study of the efficiency of WO 3 doping in various types of glasses and radiation-resistant ceramics. The prospect of the obtained data on the shielding efficiency opens up wide opportunities not only for the development of technology for creating such glasses, but also for further research in this direction in order to increase the shielding efficiency.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such high efficiency indicators, which are 1.3-2 times higher than the same for the composition 0.5TeO 2 -0.4Bi 2 O 3 -0.1WO 3 are due not only to the change in glass density, but also to the electronic configuration and vacancy density, and therefore to the value of Z e f f , which directly depends on the glass composition. The data obtained are also in good agreement with the literature data [18][19][20] devoted to the study of the efficiency of WO 3 doping in various types of glasses and radiation-resistant ceramics. The prospect of the obtained data on the shielding efficiency opens up wide opportunities not only for the development of technology for creating such glasses, but also for further research in this direction in order to increase the shielding efficiency.…”
Section: Discussionsupporting
confidence: 89%
“…At the same time, despite quite a large number of scientific works in this area of research [16][17][18][19][20][21][22][23][24][25][26][27], there are still many unresolved issues related to the search for optimal compositions and structural compounds, which will combine high absorbing and weakening ability, as well as minimum thickness. One of the promising compositions for shielding materials is a composition containing TeO 2 , Bi 2 O 3 , WO 3 , a combination of which allows obtaining high values of density, stability and values of shielding efficiency [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the excitation spectrum at 2.84 eV, 3.05 eV, and 3.18 eV showed that these bands are excited in the same energy ranges at 4.43 eV, 3.87 eV, 3, 4 eV. For pure crystals LiKSO 4 and Li 2 SO 4 we studied [14] the creation of electron-hole trapping centers. It has been shown experimentally that in pure crystals a long-wavelength recombination emission band at 3.0-3.1 eV is created, but not excited at photon energies of 5.9-6.2 eV and 9-12 eV, at which electron-hole pairs are generated.…”
Section: The Results Of the Experiments And Their Discussionmentioning
confidence: 99%
“…During the excitation of pure Na 2 SO 4 − Cu crystals two types of emission appears: intrinsic short-wavelength emission at 3.7-3.8 eV associated with the recombination of electrons with nonequivalently located holes SO − 4 ; recombination emission bands at 3.0-3.1 eV, 2.6-2.7 eV and 2.3-2.4 eV is associated with the formation of electron-hole trapping centers. Earlier, in our works [14][15][16], the nature of the recombination long-wavelength emission bands was purposefully investigated. Based on measurements of the excitation spectra for long-wavelength emission, it is shown that these recombination tunneling emissions arise at electron-hole trapping centers.…”
Section: Introductionmentioning
confidence: 99%
“…increase the concentration of impurity trapping centers. For example, in alkali metal sulfates with an admixture of the Cu + , impurity trapping centers Cu 0 − SO − 4 are created, which are responsible for the formation of an impurity dosimetric TSL peak in TLD dosimeters [14][15][16].…”
Section: Introductionmentioning
confidence: 99%